Implementation Of Digital Marketing Communication Strategies At Neostation Creative Center, Live Cooking And Coffee Bar - Tresia Wulandari; Rini Anisyahrini (Jurnal Info Sains : Informatika dan Sains, 2023)
We are currently entering an era of digitalization which is becoming a new favorite in the world of business and marketing. As if entering a new era, business actors must be able to adapt to developments in information and technology. We encounter many business actors who cannot adapt and will sink by themselves. In fact, we are often surprised by extraordinary business changes. Anti-mainstream marketing strategies to digital transactions through applications that replace cash transactions. This requires all companies, from small scale to multinational, to compete more fiercely to reach the market. As time goes by, people's lifestyles, especially in the city of Bandung, seem to be evolving. Starting from unlimited creativity with the emergence of many content creators, fulfilling a lifestyle that is not just mere socialization with the proliferation of coffee shops in the city of Bandung. This opportunity was exploited by PT. Sarana Investindo by opening a business in this field. By carrying out a minimalist creative space concept, NeoStation offers coffee shops, clothing districts, content creators, automotive enthusiasts and fashion. Seeing that most of NeoStation's target market is generation Z, namely students and business people, they must apply the Digital Marketing Concept to achieve the target. In this research we will understand how traffic, conversion and engagement work. The internet has changed the way of doing business and marketing. The data collection technique is through in-depth interviews with figures from NeoStation, conducting observations at a location located on Jalan Mutumanikam No. 69 Cijagra, Lengkong District, Bandung City, West Java, and literature review. The targeted output of this research is the accredited national journal Sinta 1-6. The proposed Technology Readiness Level is 3. The objectives of the Technology Readiness Stage that will be produced by this research are at three levels, namely, TKT 1, TKT 2 and TKT 3 with the first process knowing the basic principles of the technology that has been researched; the second is the formulation of technology concepts and their applications; the third is proof of concept in a relevant environment..